Rafting as an antipredator response of wintering White-headed Duck Oxyura leucocephala - Fox, A D; Green, A J; Hughes, B; Hilton, G (Wildfowl, 2025)
The flocking behaviour of White-headed Ducks was studied at their most important wintering site at Burdur Gl in western Turkey. Ducks fed singly by night and day in a prey-rich environment, but gathered during daylight into rafts to preen, rest and sleep, when inter-bird distances were significantly less than when feeding. Hence, rafting behaviour appears to have a predation avoidance function in the White-headed Duck, and is not related to foraging efficiency. Nearest neighbor distances declined rapidly in response to attacks from their most common predators, Herring Gulls, hence predator detection was an unlikely cause of rafting. White-headed Duck resorted to alert postures and eventually dived to avoid attacking gulls, so it was considered that predator deterrence was not responsible for flocking behaviour. Gulls singled out individual ducks which they pursued until exhausted, and were less successful where individuals could not be isolated., The length of time gulls spent harrying flocks of White-headed Duck was positively correlated to group size, and the proportion of ducks escaping from a detected predator was greater in large groups than smaller ones, hence we suggest that rafting in the White-headed Duck is primarily to dilute the predation risk from its major predator, large gulls. However, individuals also benefit from the predation confusion effect of escape by diving in association with groups of others.